A review of the Arcuphantes species with the genitalia of arcuatulus-type Araneae, Linyphiidae) - Jin, Miao; Ma, Shuangchun; Tu, Lihong (Zootaxa, 2018)
This is the second study addressing the Nearctic Arcuphantes species. Re-examination of Arcuphantes deposited in the American Museum of Natural History shows that four species have the genitalia of arcuatulus-type, including three new species: Arcuphantes arcuatulus (Roewer, 1942), A. cruciatus n. sp., A. denticulatus n. sp. and A. semiorbiculatus n. sp. Genital characters of arcuatulus-type are reviewed and compared with those of fragilis-type based on SEM images and microscopic pictures. Descriptions of the new species and a redescription of the known species are provided.